New class culture : how an emergent class is transforming America's culture - Fleishman, Avrom (Praeger, 2002)
A new class is emerging in the wake of the information economy and is altering American culture. Instead of arguing about values in aesthetic taste or morality, this book sheds new light on the culture wars by examining the social sources of recent cultural developments. Both opponents and defenders of the current cultural scene have neglected the class factors in culture generally and in present society. If the new class is added to our picture of American society, its input into the cultural marketplace helps to explain present trends in postmodernism, mixtures of high and low culture, and other recent developments.